The Influence of Corporate Social Responsibility and Free Cash Flow on Tax Avoidance in Industrial Sector Manufacturing Companies Listed on the Indonesia Stock Exchange - Mahwiyah, Mahwiyah; Krisworo, Yogo; Hakim, Lukmanul (Sean Institute, 2025)
Tax avoidance remains a crucial issue in corporate financial management, as it affects government revenue while still being legally permissible. This study aims to examine the effect of Corporate Social Responsibility (CSR) and Free Cash Flow (FCF) on tax avoidance among manufacturing companies listed on the Indonesia Stock Exchange during 2019–2023. Using a quantitative approach, the research employed panel data regression with a purposive sampling of 29 companies and data analysis conducted through EViews. The results show that CSR does not have a significant impact on tax avoidance, while FCF has a positive and significant influence, indicating that firms with higher available cash are more likely to engage in tax avoidance practices. Moreover, the joint analysis confirms that CSR and FCF simultaneously have a significant effect on tax avoidance. These findings highlight the importance of financial flexibility and corporate accountability in shaping strategic tax decisions, and contribute to the understanding of how internal and external corporate factors affect tax behavior.